Elimination Of Haemorrhagic Complications In Postoperative Thromboprophylaxis. Investigations On Heparin 2500 IU + Dhe 0.5 Mg - Buttermann, G; Haluszcynski, I; Theisinger, W; Pabst, H W (Thrombosis and Haemostasis, 1981)
Dihydroergotamine (DHE) is known to enhance the effect of low-dose heparin in the prevention of postoperative thromboembolism. In order to determine whether low-dose heparin can be reduced without decreasing the prophylactic efficacy, 350 fully randomized patients undergoing major abdominal surgery were studied by the 1-125-fibrinogen-uptake-test (RFUT) and repeated lung perfusions scintigraphy receiving either 5000 IU of heparin or 2500 IU of heparin + 0.5 mg DHE b.i.d.Results: Heparin 5000: 15 RFUT-positive (9.3%), 5 with lung perfusion defects (3.1%), 40 with haemorrhagic complications (24.8%); Heparin 2500 + DHE: 13 RFUT-positive (8.0%), 4 with lung perfusion defects (2.5%), 8 with haemorrhagic complications (4.9%), the difference in bleeding complications is highly significant (p < 0.001).Conclusions: The combination of heparin 2500 IU + DHE 0.5 mg b.i.d. proved equivalent to heparin 5000 IU b.i.d. in terms of antithrombotic efficacy, whereas bleeding complications due to prophylaxis (wound haematoma, postoperative bloodloss, reoperations because of haemorrhage) were significantly reduced. Altogether this combination turns out an important progress in the postoperative thromboprophylaxis.